THE INFLUENCE OF MORPHOLOGICAL AWARENESS INSTRUCTION ON VOCABULARY DEVELOPMENT OF INDONESIAN ESL LEARNERS - Waziana, Winia; Rohmatillah, Rohmatillah (Raden Intan State Islamic University of Lampung, Indonesia, 2025)
This study investigates the influence of morphological awareness instruction on the vocabulary development of Indonesian ESL learners through a quasi-experimental design. It involved 60 participants divided into an experimental group that received explicit instruction about morphemes—prefixes, suffixes, and roots—and a control group following the conventional vocabulary curriculum. Statistical analyses, including normality tests, homogeneity tests, and t-tests, were employed to assess vocabulary gains. Results indicate a significant improvement in vocabulary scores for the experimental group (M = 78.5, SD = 5.4) compared to the control group (M = 67.2, SD = 6.1) with excellent statistical significance (p < 0.001). These findings suggest that explicit morphological awareness instruction significantly enhances vocabulary comprehension and retention among Indonesian ESL learners, providing insights into effective linguistic strategies that can enrich vocabulary development in language learning contexts